Highly selective inhibitors of protein kinases CLK and HIPK with the furo[3,2-b]pyridine core - Němec, Václav; Maier, Lukáš; Berger, Benedict-Tilman; Chaikuad, Apirat; Drápela, Stanislav; Souček, Karel; Knapp, Stefan; Paruch, Kamil (European journal of medicinal chemistry, 2021)
The furo [3,2-b]pyridine motif represents a relatively underexplored central pharmacophore in the area of kinase inhibitors. Herein, we report flexible synthesis of 3,5-disubstituted furo [3,2-b]pyridines that relies on chemoselective couplings of newly prepared 5-chloro-3-iodofuro [3,2-b]pyridine. This methodology allowed efficient second-generation synthesis of the state-of-the-art chemical biology probe for CLK1/2/4 MU1210, and identification of the highly selective inhibitors of HIPKs MU135 and MU1787 which are presented and characterized in this study, including the X-ray crystal structure of MU135 in HIPK2. chemical biology probe.
Keywords: Protein Binding; MU1210; protein-serin-threoninkinasy; krystalografie rentgenová; HIPK; MU1787; Structure-Activity Relationship; Protein Serine-Threonine Kinases; molekulární struktura; Molecular Structure; Inhibitor; MU135; CLK; furany; inhibitory proteinkinas; Furo[3,2-b]pyridine; MFC-7 buňky; Crystallography, X-Ray; vztahy mezi strukturou a aktivitou; MCF-7 Cells; Carrier Proteins; Kinase; vazba proteinů; Animals; lidé; Humans; zvířata; pyridiny; Protein Kinase Inhibitors; myši; Pyridines; Mice; Furans; transportní proteiny